Four new species and eighteen lectotypifications of Larnax from Ecuador and Peru and a new synonym of Deprea orinocensis (Solanaceae: Solanoideae, Physalideae) - Deanna, Rocío (2014)
Four new species of Larnax, L. macasiana, L. pumila, L. purpureocarpa, and L. toledoana, are described and illustrated and species conservation assessments presented. Eighteen lectotypifications (Larnax abra-patriciae, L. altomayoense, L. bongaraense, L. chotanae, L. dilloniana, L. kann-rasmusseniorum, L. longipedunculata, L. lutea, L. nieva, L. pedrazae, L. peruviana, L. pilosa, L. pomacochaense, L. purpurea, L. sagasteguii, L. sawyeriana, L. schjellerupiae, and L. vasquezii) of Peruvian Larnax are proposed mainly to replace material destroyed in a fire at HAO (Trujillo, Peru). A new synonym of Deprea orinocensis from Ecuador, Iochroma suffruticosum is also proposed and lectotypified based on an examination of original type material.